Coded excitation ultrasonic needle tracking: An in vivo study - Xia, Wenfeng; Ginsberg, Yuval; West, Simeon J.; Nikitichev, Daniil I.; Ourselin, Sebastien; David, Anna L.; Desjardins, Adrien E. (Medical physics (Lancaster), 2016)
Purpose: Accurate and efficient guidance of medical devices to procedural targets lies at the heart of interventional procedures. Ultrasound imaging is commonly used for device guidance, but determining the location of the device tip can be challenging. Various methods have been proposed to track medical devices during ultrasound-guided procedures, but widespread clinical adoption has remained elusive. With ultrasonic tracking, the location of a medical device is determined by ultrasonic communication between the ultrasound imaging probe and a transducer integrated into the medical device. The signal-to-noise ratio (SNR) of the transducer data is an important determinant of the depth in tissue at which tracking can be performed. In this paper, the authors present a new generation of ultrasonic tracking in which coded excitation is used to improve the SNR without spatial averaging. Methods: A fiber optic hydrophone was integrated into the cannula of a 20 gauge insertion needle. This transducer received transmissions from the ultrasound imaging probe, and the data were processed to obtain a tracking image of the needle tip. Excitation using Barker or Golay codes was performed to improve the SNR, and conventional bipolar excitation was performed for comparison. The performance of the coded excitation ultrasonic tracking system was evaluated in an in vivo ovine model with insertions to the brachial plexus and the uterine cavity. Results: Coded excitation significantly increased the SNRs of the tracking images, as compared with bipolar excitation. During an insertion to the brachial plexus, the SNR was increased by factors of 3.5 for Barker coding and 7.1 for Golay coding. During insertions into the uterine cavity, these factors ranged from 2.9 to 4.2 for Barker coding and 5.4 to 8.5 for Golay coding. The maximum SNR was 670, which was obtained with Golay coding during needle withdrawal from the brachial plexus. Range sidelobe artifacts were observed in tracking images obtained with Barker coded excitation, and they were visually absent with Golay coded excitation. The spatial tracking accuracy was unaffected by coded excitation. Conclusions: Coded excitation is a viable method for improving the SNR in ultrasonic tracking without compromising spatial accuracy. This method provided SNR increases that are consistent with theoretical expectations, even in the presence of physiological motion. With the ultrasonic tracking system in this study, the SNR increases will have direct clinical implications in a broad range of interventional procedures by improving visibility of medical devices at large depths.